The Role of Agribusiness in Facilitating Farmers’Access to Carbon Markets - Sadiq, Sanusi Mohammed; Paul Singh, Invinder; Makarfi Ahmad, Muhammad; Sanyinna Sani, Bashir (New Countryside, 2025)
Climate change presents a growing global challenge, necessitating innovative solutions to reduce greenhouse gas (GHG) emissions. One such approach is the development of carbon markets, which incentivize emission reductions by allowing entities to trade carbon credits. Farmers, as key stakeholders in climate mitigation efforts, possess the potential to contribute significantly to carbon sequestration and emission reductions through sustainable agricultural practices. However, despite this potential, their participation in carbon markets remains constrained by several barriers. These include a lack of technical knowledge, the high costs associated with market entry and compliance, and the overall complexity of the carbon trading system. To address these challenges, agribusiness entities have emerged as essential intermediaries, facilitating farmers’ integration into carbon markets. By offering capacity-building initiatives, financial support, and streamlined market access, agribusiness firms play a crucial role in bridging the gap between farmers and carbon credit trading platforms. Their involvement can lower transaction costs, provide necessary technical guidance, and create efficient channels for farmers to monetize sustainable agricultural practices. This review explores the theoretical frameworks underpinning agribusiness participation in carbon markets, presents case studies highlighting successful interventions, and examines recent developments in policy and technology. It further recommends strategic reforms, technological advancements, and multi-stakeholder collaborations to enhance the effectiveness of agribusiness in facilitating farmers’ engagement with carbon markets.